Behavior evaluation of geogrid-reinforced ballast-subballast interface under shear condition. Issue 1 (February 2019) - Sweta, Kumari; Hussaini, Syed Khaja Karimullah
Abstract: The effective functioning of a railway track under operating conditions depends largely on the performance of various rail track interfaces (e.g. ballast-subballast interface, subballast-subgrade interface). In this context, a series of large-scale direct shear tests were conducted to investigate the shear behavior of unreinforced and geogrid-reinforced ballast-subballast interfaces at different normal stresses ( σ n ) and rates of shearing ( S r ). Fresh granite ballast and subballast having average particle size ( D 50 ) of 42 mm and 3.5 mm respectively, and five geogrids with different aperture shapes and sizes were used in this study. Tests were performed at different normal stresses ( σ n ) ranging from 20 to 100 kPa and shearing rates ( S r ) ranging from 2.5 to 10.0 mm/min. The laboratory test results confirmed that the shear strength of ballast-subballast interface was highly influenced by the applied normal stress ( σ n ) and rate of shearing ( S r ). The friction angle ( φ ) of unreinforced ballast-subballast interface was found to decrease from 63.24° to 47.82° and dilation angle ( ψ ) from 14.56° to 5.23° as the values of σ n and S r increased from 20 to 100 kPa and 2.5–10.0 mm/min, respectively. Further, the breakage of ballast ( B g ) was found to increase from 2.84 to 6.69%. However, geogrid inclusions enhanced the shear strength of the ballast-subballast interface and also reduced the extent of B g . The results indicate that it is possible to establish a relationship between the friction angle ( φ ) and breakage of ballast ( B g ), wherein the friction angle ( φ ) of both unreinforced and geogrid-reinforced interfaces reduces with the increase in breakage ( B g ). The interface efficiency factor, defined as the ratio of the shear strength of the geogrid-reinforced ballast-subballast interface to the original shear strength of ballast-subballast interface varies from 1.04 to 1.22. Moreover, the current study revealed that the shear behavior of ballast-subballast interface was influenced by geogrid aperture size ( A ).